Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4103/0972-0707.157260
|View full text |Cite
|
Sign up to set email alerts
|

Root and canal morphology of maxillary first premolar teeth in north Indian population using clearing technique: An in vitro study

Abstract: Aim:The purpose of this study was to determine the root form and canal configuration in maxillary first premolars.Materials and Methods:A total of 250 extracted human adult maxillary first premolar teeth from North Indian population were collected. Access cavities were prepared and the coronal pulp tissue was extirpated. The samples were stored in 5% nitric acid solution for 5 days. They were then rinsed, dried, and dehydrated using increasing concentrations of ethanol (70, 80, and 95%) successively for 1 day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 25 publications
(31 reference statements)
4
38
5
Order By: Relevance
“…Similar findings were observed in studies by Carns EJ et al (12), Vertucci FJ et al (13) The results of our analysis support these statements. However, there are studies in which the upper first premolar usually had one root (14). Three roots, which is described as a rare phenomenon, were not observed in our study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Similar findings were observed in studies by Carns EJ et al (12), Vertucci FJ et al (13) The results of our analysis support these statements. However, there are studies in which the upper first premolar usually had one root (14). Three roots, which is described as a rare phenomenon, were not observed in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Three roots, which is described as a rare phenomenon, were not observed in our study. However, some authors described that the upper first premolar may have three roots in a very limited percentage of subjects (1,4,14).…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been shown to be more accurate than digital radiographs in determining root canal systems and can also evaluate the canal configuration in vivo, thereby useful in clinical assessment. Neelakantan et al 10 reported that CBCT can detect the root canal system as accurately as canal staining and clearing techniques. 11 Maxillary premolars have a complex and highly variable anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…1 The variation in number of roots and canal configuration makes endodontic treatment on these teeth complex. 10 Different studies have reported variations in canal configurations in maxillary first premolars. 10 Vertucci in 1984 studied the canal configuration of human permanent teeth and reported that maxillary first premolar was the only tooth which had all the eight types of canal configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation